A Checklist of the Bryobionta of Ukraine (taxonomic review, superspecies taxa) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
The results of the review of superspecies taxons of Ukraine Bryophyta according to the «A Checklist of mossesa of Ukraine (2008)» are given in the article: superdivision, division, classes, orders, families, genera. Due to July, 30, 2008 superdivision Bryobionta includes 3 divisions of 8 classes 29 orders 83 families 253 genera. Among them 2 genera 1 family 1 order 1 class refer to Anthocerotophyta division, 61 genera 32 families 10 orders 2 classes refer to Marchantiophyta division and 190 genera 50 families 18 orders 5 classes refer to Bryophyta division.
Keywords: checklist, Bryobionta, Anthocerotophyta, Marchantiophyta, Bryophyta, Ukraine.